Cervical human papillomavirus detection is not affected by menstrual phase. Issue 3 (30th October 2012) - Tota, Joseph E; Ramanakumar, Agnihotram V; Mahmud, Salaheddin M; Trevisan, Andrea; Villa, Luisa L; Franco, Eduardo L; ,
Abstract : Objectives: In many settings, human papillomavirus (HPV) DNA testing already plays an important role in cervical cancer screening. It is unclear whether hormonal fluctuations associated with menstrual phase or oral contraceptive (OC) use have any effect on HPV detection. We evaluated the effects of OC use and timing of cervical sampling in relation to women's last menstrual period (LMP) on HPV detection, and viral load in the Brazilian Ludwig–McGill cohort study. Methods: Women in the cohort were followed every 4–6 months, and at each clinic visit they were asked to complete a questionnaire and to provide a cervical sample for HPV testing. Specimens from 6093 patient visits (n=2209 women) were categorised according to date of LMP into four distinct phases: follicular (days 5–9), midcycle (days 10–15), luteal (days 16–22), or late luteal (days 23–31). Results: Compared with follicular phase (referent group), HPV detection did not differ according to reported LMP for midcycle (OR=1.14, 95% CI 0.95 to 1.37), luteal (OR=1.03, 95% CI 0.85 to 1.25), or late luteal menstrual phase (OR=1.01, 95% CI 0.83 to 1.24), and was also not influenced by OC use. Analyses restricted to high-risk HPV types (grouped) and HPVs 16 and 18 (separately), produced similar non-significant associations. For HPV-positive samples, we found that the menstrual phase did not influence the total viral load. Conclusions: These results indicate HPV detection is not associated with menstrual phase. Our findings suggest that standardising the timing of specimen collection for HPV testing is not necessary.